(untitled) (Journal of Academic Research, 2025)
This study explores the preparation and characterization of solid co-crystals of sulfamethoxazole (SMZ) and trimethoprim (TMP) to enhance their pharmaceutical properties, particularly solubility and stability. SMZ-TMP co-crystals were successfully obtained using methanol, while a salt form emerged in tetrahydrofuran (THF), demonstrating solvent-dependent behavior. Various characterization techniques, including Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), and Powder X-ray Diffraction (PXRD), were employed to confirm the formation and properties of the co-crystals. The SMZ-TMP co-crystal exhibited improved thermal stability and distinct molecular interactions, as evidenced by changes in FTIR hydrogen-bonding regions and thermal analysis.